Yuval Noah Harari, from Animals into Gods. A Brief History of Humankind. Bogotá: Penguin Random House, 2017 - López González, Rosendo; Ramírez Valencia, Astrid (Visión electrónica, 2020)
Yuval Noah Harari, from Animals into Gods